2020
DOI: 10.1007/s10648-020-09580-8
|View full text |Cite
|
Sign up to set email alerts
|

A Commentary on Bowers (2020) and the Role of Phonics Instruction in Reading

Abstract: Bowers (2020) reviewed 12 meta-analytic syntheses addressing the effects of phonics instruction, concluding that the evidence is weak to nonexistent in supporting the superiority of systematic phonics to alternative reading methods. We identify five issues that limit Bowers' conclusions: 1. Definition issues; 2. What is the right question? 3. The assumption of "phonics first"; and 4. Simplification of issues around systematic versus explicit phonics. We then go on to consider 5. Empirical issues in the data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 50 publications
1
23
0
2
Order By: Relevance
“…A recent meta-analysis of 20 experimental and quasiexperimental K-12 classroom studies (Graham & Santangelo, 2014; see also Graham & Hebert, 2010) comparing spelling instruction against no instruction or other learning interventions that did not focus directly on spelling (e.g., Kirk & Gillon, 2009;Ouellette et al, 2013;Rieben et al, 2005) found that spelling instruction was associated with improved reading skills. However, the conclusions of the meta-analytic literature on spelling-focused instruction and reading skills have recently been criticized on methodological and interpretative grounds (for discussion, see Bowers, 2020;Fletcher et al, 2020), which heightens the need for more research to verify the efficacy of such instructional methods. Moderate-to-high correlations of r = 0.5-0.9 between spelling and reading test scores have also been observed across multiple studies (e.g., Ehri, 1987;Townsend, 1947; for discussions see Graham et al, 2002;Rayner et al, 2001;Shankweiler & Lundquist, 1992), indicating potential links between the two skill domains, but a causal relationship cannot be inferred from such data.…”
Section: Evidence Of Links Between Spelling Reading and Writing Skillsmentioning
confidence: 99%
“…A recent meta-analysis of 20 experimental and quasiexperimental K-12 classroom studies (Graham & Santangelo, 2014; see also Graham & Hebert, 2010) comparing spelling instruction against no instruction or other learning interventions that did not focus directly on spelling (e.g., Kirk & Gillon, 2009;Ouellette et al, 2013;Rieben et al, 2005) found that spelling instruction was associated with improved reading skills. However, the conclusions of the meta-analytic literature on spelling-focused instruction and reading skills have recently been criticized on methodological and interpretative grounds (for discussion, see Bowers, 2020;Fletcher et al, 2020), which heightens the need for more research to verify the efficacy of such instructional methods. Moderate-to-high correlations of r = 0.5-0.9 between spelling and reading test scores have also been observed across multiple studies (e.g., Ehri, 1987;Townsend, 1947; for discussions see Graham et al, 2002;Rayner et al, 2001;Shankweiler & Lundquist, 1992), indicating potential links between the two skill domains, but a causal relationship cannot be inferred from such data.…”
Section: Evidence Of Links Between Spelling Reading and Writing Skillsmentioning
confidence: 99%
“…However, the conclusions of the meta-analytic literature on spelling-focused instruction and reading skills have recently been criticized on methodological and interpretative grounds (for discussion see Bowers, 2020;Fletcher et al, 2020), which heightens the need for more research to verify the efficacy of such instructional methods. Moderate-to-high correlations of r = 0.5-0.9 between spelling and reading test scores have also been observed across multiple studies (e.g., Ehri, 1987;Townsend, 1947; for discussions see Graham et al, 2002;Rayner et al, 2001;Shankweiler & Lundquist, 1992), indicating potential links between the two skill domains, but a causal relationship cannot be inferred from such data.…”
Section: Evidence Of Links Between Spelling Reading and Writing Skillsmentioning
confidence: 99%
“…Even the most optimistic supporters of current phonics programmes note that effects have ‘plateaued’ in recent years and at least 15% of children do not currently achieve even the relatively narrow current Key Stage 1 benchmarks, and the persistence of a long tail of under‐achievement in the Progress in International Reading Literacy Study (PIRLS) (2016) international comparisons for older text readers in year 5 (e.g., Stainthorp, 2020). The teaching of phonics has thus been, and continues to be, the subject of public debate (e.g., Barrs et al, 2008; Fletcher et al, 2021; Kirby and Savage, 2008; Savage and Cloutier, 2017; Wyse and Bradbury, 2022).…”
Section: Introductionmentioning
confidence: 99%